PENGARUH SOLVABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saeful Fachri; Willy Nurhayadi; Rini Softiani; Anistya Vinta Desi (LP2M Universitas Bina Bangsa, 2024)
This study was conducted to determine the influence of solvency, liquidity, and company size on financial performance in manufacturing companies in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The data source used is a secondary data source with data collection techniques through the www.idx.co.id website. The sampling technique uses a saturated sampling technique, totaling 15 samples which are manufacturing companies in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The data analysis method used in this study is quantitative data analysis. The results of the descriptive analysis show that the solvency, liquidity, and size of the company on the financial performance of manufacturing companies in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period are relatively low, because the four variables are on a valuation scale of 0.20 – 0.399. The results of the hypothesis test partially show that solvency has a positive and significant effect on financial performance. Liquidity has a positive and significant effect on financial performance. And the size of the company does not have a significant effect on financial performance. The conclusion of this study is that there is a simultaneous (together) influence between the variables of solvency, liquidity, and company size on financial performance in manufacturing companies in the plastic and packaging sub-sector listed on the Indonesia Stock Exchange for the 2021-2022 period